2022
DOI: 10.1186/s40337-022-00567-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring perceived training and professional development needs of Australian dietetic students and practising dietitians in the area of eating disorders: a focus group study

Abstract: Background Timely diagnosis and treatment of eating disorders (EDs) are essential for achieving the best possible outcomes, and dietitians have an important role in the multidisciplinary team. ED-specific training has been shown to enhance the knowledge, mental health literacy and confidence of health professionals in providing patient treatment. However, the ED-specific training needs of dietitians have yet to be determined. This study aimed to explore the perceived readiness of dietitians and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 44 publications
(48 reference statements)
3
12
0
Order By: Relevance
“…These findings are consistent with earlier work by Trammell et al [ 29 ] who have also reported that ED-specific lectures in the United States were limited to a brief introduction to EDs, with little information on dietetic treatment approaches [ 29 ]. In Australia, the authors have previously reported that both practising dietitians and final year dietetic students perceive the current ED-specific education and training at universities to be inadequate [ 5 ]. In this previous study [ 5 ], the authors recommended augmenting the ED-specific education and training components within all university programs, beyond an introductory level, to enhance the preparedness of dietitians to practice in this clinical area and reduce their general reluctance to treat patients with an ED.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent with earlier work by Trammell et al [ 29 ] who have also reported that ED-specific lectures in the United States were limited to a brief introduction to EDs, with little information on dietetic treatment approaches [ 29 ]. In Australia, the authors have previously reported that both practising dietitians and final year dietetic students perceive the current ED-specific education and training at universities to be inadequate [ 5 ]. In this previous study [ 5 ], the authors recommended augmenting the ED-specific education and training components within all university programs, beyond an introductory level, to enhance the preparedness of dietitians to practice in this clinical area and reduce their general reluctance to treat patients with an ED.…”
Section: Discussionmentioning
confidence: 99%
“…However, these competency standards [ 3 , 4 ] do not include explicit guidance on the role of the dietitian in treating people with specific clinical conditions. Increasingly, this issue has been perceived as a considerable barrier by both dietetic students and qualified dietitians in building their confidence to practice in complex clinical areas, such as eating disorders (EDs) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reveal a lack of confidence among dietitians and reluctance to provide care for EDs [ 27 29 ]. Reasons for this include a perceived lack of training provided during university, limited understanding of scope of practice and role of dietitians within the treating team, and a poor understanding of EDs and co-occurring mental health conditions [ 30 , 31 ]. Ongoing professional development, education and supervision are recommended for dietitians working in this practice area [ 13 ].…”
Section: Discussionmentioning
confidence: 99%